The Great Santini - Carlino, Lewis John 1932- .; Conroy, Pat 1945- .; Pratt, Charles A. 1923-2005; Duvall, Robert 1931- .; Danner, Blythe 1943.; O'Keefe, Michael 1955- .; Warner Bros. (Burbank, California Warner Home Video, 1999)
Bull Meechum is a hard case, a fighter pilot so killed that he's called The Great Santini. But now it's peacetime 1962. And more at home playing "top gun" in the cockpit than father in hid living room, he's become that most useless figure: a warrior without a war.
Robert Duvall, Blythe Danner, Michael O'Keefe, Stan Shaw.
DVD (Region 1, NTSC) ; Standard version ; Dolby digital.
In English.
Keywords: Soldiers -- Family relationships -- Drama; Feature films